Literasi Perpajakan, Kesadaran Perpajakan, dan Kepatuhan Pajak Kendaraan Bermotor Dengan Financial Technology Sebagai Mediator - Erdi, Tio Waskito; Astuti, Ratna Puji (E-Jurnal Akuntansi, 2023)
This research investigates the influence of tax literacy and tax awareness among students in Yogyakarta on motor vehicle tax compliance. Fintech plays an important role in increasing tax compliance. Therefore, in this research we will place Fintech as a mediating variable, which has not received attention in previous research. The sample was determined using a purposive sampling technique with a total sample of 178 respondents. This research uses descriptive demographic statistical analysis and PLS-SEM. The research results explain fintech as a mediating variable in the relationship between tax literacy and tax awareness on motor vehicle tax compliance. Consistent with previous research and confirming the Theory of Planned Behavior which explains that individuals who have good tax literacy and tax awareness have a positive attitude towards motor vehicle tax compliance. Keywords: Tax Literacy; Tax Awareness; Financial Technology; Tax Compliance